Gereja Transtemporal: Melihat Kembali Kesatuan Orang Mati, Hidup, dan Belum Lahir sebagai Communio Sanctorum - Sitanggang, Eunice Abigail (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2023)
The unity of the church across time is implied in the introductory sentence before the recitation of the Apostles’ Creed in a typical church service. However, it seems that it is still not clearly discussed in the church; thus it is still very opaque when people are asked to explain the position of the dead, the living, and the unborn as a community. This paper aims to discuss the unity of Christian fellowship across time; that is, the participation of the dead and the unborn in Christian fellowship. The author argues that the Christian community encompasses all three: the dead, the living, and the future as one. By comparing the concept of communio sanctorum from Dietrich Bonhoeffer and Elizabeth Johnson, as well as time encompassing past, present, and future, the author builds a conversation about the church as a transtemporal community.